An improved fast watershed algorithm for image segmentation. (19th January 2011) - Suphalakshmi, A.; Narendran, S.; Anandhakumar, P.
Connected component based on chain codes is a simple and effective method to implement watersheds based on rainfall simulation. However, time complexity of existing algorithm based on chain code remained high as it scans the image four times. In this paper, we propose an improved fast watershed algorithm, which scans the image only twice, one for generating connected components and other for labelling the catchment basins. Experimental results show that proposed algorithm produces expected results twice faster than existing algorithm.